The Role of Publicly Provided Electricity in Economic Development: The Experience of the Tennessee Valley Authority, 1929–1955. (16th May 2014) - Kitchens, Carl
<x content-type="archive" xml:space="preserve">Abstract</x> I study the impacts of one of the largest regional development projects in American History, the Tennessee Valley Authority (TVA), on a variety of economic outcomes. The TVA has been noted as an example of how to develop a region's water power potential to stimulate growth. In what follows, I show using a county-level panel dataset, that the TVA had little impact on economic growth in the South. I attribute these results to the institutional history of the TVA and the contractual agreements it signed in an effort to expand its service territory. "…as a pebble dropped in a pond causes ripples to flow outward to the surrounding shores, the influence of TVA'slow rates flows outward to surrounding areas…" TVA's Influence on Electric Rates 1965